1001 golf holes you must play before you die - Barr, Jeff (Cassell Illustrated, 2012)
Every golfer longs for the opportunity to play as many great golf holes as possible. Fully updated for 2012 it contains over 800 illustrations from international golf courses across the world, 1001 Golf Holes is a truly comprehensive guide to the world's ultimate golf holes. Fact boxes provide instant information on the course, location, architect, designer, length and par of each hole, while longer entries give further insight into playing the hole, the designer's intention and the history of the greats who have played there.